Digital chain for pelvic tumor resection with 3D-printed surgical cutting guides - Biscaccianti, Vincent; Fragnaud, Henri; Hascoët, Jean-Yves; Crenn, Vincent; Vidal, Luciano (Frontiers in Bioengineering and Biotechnology, 2022)
Surgical cutting guides are 3D-printed customized tools that help surgeons during complex surgeries. However, there does not seem to be any set methodology for designing these patient-specific instruments. Recent publications using pelvic surgical guides showed various designs with no clearly classified or standardized features. We thus developed a systematic digital chain for processing multimodal medical images (CT and MRI), designing customized surgical cutting guides, and manufacturing them using additive manufacturing. The aim of this study is to describe the steps in the conception of the surgical cutting guides used in complex oncological bone tumor pelvic resection. We also analyzed the duration of the surgical cutting guide process and tested its ergonomics and usability with orthopedic surgeons using Sawbones models on simulated tumors. The original digital chain made possible a repeatable design of customized tools in short times. Preliminary testing on synthetic bones showed satisfactory results in terms of design usability. The four artificial tumors (Enneking I, Enneking II, Enneking III, and Enneking I+IV) were successfully resected from the Sawbones model using this digital chain with satisfactory ergonomic outcomes. This work validates a new digital chain conception and production of surgical cutting guides. Further works with quantitative margin assessments on anatomical subjects are needed to better assess the design implications of patient-specific surgical cutting guide instruments in pelvic tumor resections.